Photothermally sensitive gold nanocage augments the antitumor efficiency of immune checkpoint blockade in immune “cold” tumors - Xiao, Guixiu; Zhao, Yujie; Wang, Xueyan; Zeng, Chuan; Luo, Feng; Jing, Jing (Frontiers in Immunology, 2023)
Introduction Immune checkpoint blockade (ICB) has revolutionized the therapy landscape of malignancy melanoma. However, the clinical benefits from this regimen remain limited, especially in tumors lacking infiltrated T cells (known as “cold” tumors). Nanoparticle-mediated photothermal therapy (PTT) has demonstrated improved outcomes in the ablation of solid tumors by inducing immunogenic cell death (ICD) and reshaping the tumor immune microenvironment. Therefore, the combination of PTT and ICB is a promising regimen for patients with “cold” tumors. Methods A second near-infrared (NIR-II) light-activated gold nanocomposite AuNC@SiO2@HA with AuNC as a kernel, silica as shell, and hyaluronic acid (HA) polymer as a targeting molecule, was synthesized for PTT. The fabricated AuNC@SiO2@HA nanocomposites underwent various in vitro studies to characterize their physicochemical properties, light absorption spectra, photothermal conversion ability, cellular uptake ability, and bioactivities. The synergistic effect of AuNC@SiO2@HA-mediated PTT and anti-PD-1 immunotherapy was evaluated using a mouse model of immune “cold” melanoma. The tumor-infiltrating T cells were assessed by immunofluorescence staining and flow cytometry. Furthermore, the mechanism of AuNC@SiO2@HA-induced T-cell infiltration was investigated through immunochemistry staining of the ICD-related markers, including HSP70, CRT, and HMGB1. Finally, the safety of AuNC@SiO2@HA nanocomposites was evaluated in vivo. Results The AuNC@SiO2@HA nanocomposite with absorption covering 1064 nm was successfully synthesized. The nano-system can be effectively delivered into tumor cells, transform the optical energy into thermal energy upon laser irradiation, and induce tumor cell apoptosis in vitro. In an in vivo mouse melanoma model, AuNC@SiO2@HA nanocomposites significantly induced ICD and T-cell infiltration. The combination of AuNC@SiO2@HA and anti-PD-1 antibody synergistically inhibited tumor growth via stimulating robust T lymphocyte immune responses. Discussion The combination of AuNC@SiO2@HA-mediated PTT and anti-PD-1 immunotherapy proposed a neoteric strategy for oncotherapy, which efficiently convert the immune “cold” tumors into “hot” ones.